THE EVALUATION OF PUBLIC HEARING FOR NATIONAL HEALTH SECURITY SYSTEM, NATIONAL HEALTH SECURITY OFFICE (NHSO), REGION 1, THAILAND - สิทธิสันติกุล, เกศสุดา; คำศรีจันทร์, วิรัตน์; โจลานันท์, บัญจรัตน์; ยศสุข, ปรารถนา (Academic Journal Phranakhon Rajabhat University, 2019)
This study aimed to evaluate inputs, process, products and contexts, and to analyze preference level of participants under public hearing for national health security system conducted by National Health Security Office (NHSO), Region 1. Qualitative data from document analysis, participatory observation, and 58 interviewees were analyzed for evaluating inputs, process, products and contexts. Quantitative data for analyzing level of preference were also derived by questionnaires with 450 participants. The results indicated that 1) inputs – policy and strategy for development of national health security system, and act of national health security 2006, 2) process – planning, implementation and evaluation, 3) products – outputs: the results of public hearings for policy and implementation ; outcomes: stimulating sense of health care and service 4) contexts – strengths: structural management, networking ; weaknesses: participants, issues of public hearing, communication, lifting opinions to policy ; opportunities: policy, law, networking, public awareness ; threatens: national structure, financial regulations, access to local administrative organization and ethnics 5) preference level – good level in process, participation, and issues of public hearing being.